1984
DOI: 10.2151/jmsj1965.62.2_343
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical and Dynamical Contributions to the Seasonal Variation of Total Ozone Amount over Japan

Abstract: The latitudinal and seasonal variations of ozone photochemical process are analyzed using the monthly means of ozone density observed by ozonesondes at Sapporo, Tateno and Kagoshima.The estimated photochemical change rate (creation minus destruction) and observed ozone density variation are used to evaluate the divergence of ozone.The seasonal variation of total ozone amount at Kagoshima is mainly due to the density variation in the quasi steady region, where the photochemical change rate of ozone density is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As is wellknown, total ozone amounts (vertically integrated ozone mass) are much larger on the polar side of the subtropical jet stream than on the equatorial side, reflecting the difference in the tropopause height. Iwasaki and Kaneto (1984) showed that the altitude of the tropopause primarily determines the seasonal variation of total ozone amounts in midlatitudes. In the control run without GWD schemes, the tropopause height in mid-latitudes (northern side of the subtropical jet stream) cannot be maintained realistically, but it becomes higher with the forecast period because cooling biases in the lower stratosphere reduce static stability just above the tropopause.…”
Section: 3 Effects Of Gwd On Me Dower-stratosphere Tracermentioning
confidence: 99%
“…As is wellknown, total ozone amounts (vertically integrated ozone mass) are much larger on the polar side of the subtropical jet stream than on the equatorial side, reflecting the difference in the tropopause height. Iwasaki and Kaneto (1984) showed that the altitude of the tropopause primarily determines the seasonal variation of total ozone amounts in midlatitudes. In the control run without GWD schemes, the tropopause height in mid-latitudes (northern side of the subtropical jet stream) cannot be maintained realistically, but it becomes higher with the forecast period because cooling biases in the lower stratosphere reduce static stability just above the tropopause.…”
Section: 3 Effects Of Gwd On Me Dower-stratosphere Tracermentioning
confidence: 99%
“…This AO evolution in the NH mid-latitude lower stratosphere is determined by the QSW structure in Fig. 3a (see also [23,32,35]). The two months later (September-October), annual minimum is observed in region of zonal minimum and in zonal mean (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…6r is evidence of the QSW structure influence. The specificity of AO here depends on the relationship between the rates of the processes of dynamical ozone accumulation (the larger effect of meridional circulation in autumn-winter) and photochemical relaxation (spring-summer) in the region of the quasi-stationary maximum of total ozone [2,23,32,35]. As a result, the AO extrema in the Longfengshan domain appear 2-3 months earlier than in the region of the zonal TOC minimum: April and October-November, respectively [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations